Proceedings of the 3rd Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2018) 2018
DOI: 10.2991/aisteel-18.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

The Difference Between Certified And Non Certified PE Teachers Performance Based On Range Of Service Period

Abstract: There are four competencies that should be owned by a teacher, pedagogic, personality, professional and social. Low compensation will make performance low and vice versa. If the compensation is high, it will make the performance high. The certification allowance given to the teacher for one months salary is a form of compensation to the teacher. Based on the result of performance appraisal conducted by the District Education of Deli Serdang (School Supervisor), the data of physical education teachers performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The questions were related to the job satisfaction level of PE teachers, which was far beyond the level of satisfaction ( Lami, 2018 ). As a result, teachers of PE classes had low performance ( Sinulingga and Simatupang, 2018 ). For this reason, most of the students lack interest in attending PE classes ( Trigueros et al, 2019 ; Seidu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questions were related to the job satisfaction level of PE teachers, which was far beyond the level of satisfaction ( Lami, 2018 ). As a result, teachers of PE classes had low performance ( Sinulingga and Simatupang, 2018 ). For this reason, most of the students lack interest in attending PE classes ( Trigueros et al, 2019 ; Seidu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, most of the students did not attend PE classes because of a lack of interest and motivation ( Trigueros et al, 2019 ; Seidu et al, 2020 ). There were many reasons for the low production level of PE teachers in terms of performance ( Sinulingga and Simatupang, 2018 ). One of the key reasons behind the low performance was the incompetence of PE teachers in conducting classes of PE ( Yilmaz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhodomyrtus tomentosa has been identified to contain antioxidants that are useful for the human body. Other studies revealed that crushed leaves of R. tomentosa are useful for healing wounds (Sinulingga et al 2018;Vo and Ngo 2019).…”
Section: Composition Of Medicinal Plants By Familymentioning
confidence: 99%
“…Pada 5 Uji Signifikansi Parsial (Statistik t) menunjukkan hasil pengujian statistik bahwa nilai signifikan lebih kecil dari α = 0,05 (0,014 < 0,05) artinya ASEAN Corporate Governance Scorecard (ACGS) memiliki pengaruh terhadap asimetri informasi. Hal ini dikarenakan semakin meningkatnya penerapan prinsip-prinsip ACGS di Indonesia terlihat dari peringkat ACGS Indonesia pada 2017 mengalami perbaikan sejak 2015 dari rata-rata nilai negara 62,88 menjadi 70,59 [7]. Hasil penilaian tahun 2017 terhadap 100 perusahaan Indonesia yang tercatat di Bursa Efek Indonesia menunjukkan perbaikan yang signifikan pada tiga (3) aspek, yakni: Pertama, hakhak pemegang saham, yaitu perusahaan telah mengungkapkan praktiknya untuk mendorong pemegang saham lebih terlibat di perusahaan di luar rapat umum pemegang saham tahunan.…”
Section: Pembahasanunclassified